2023
DOI: 10.3390/jcm12041671
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and Evaluation of Outcomes of Ureteroscopy and Stone Laser Fragmentation in Extremes of Age Groups (≤10 Years and ≥80 Years of Age): A Retrospective Comparative Analysis of over 15 Years from 2 Tertiary European Centres

Abstract: Aim: To assess and compare the outcomes associated with ureteroscopy and laser fragmentation (URSL) for extremes of age group (≤10 and ≥80 years). Methods: Retrospective consecutive data were collected from two European centres for all paediatric patients ≤10 undergoing URSL over a 15-year period (group 1). It was compared to consecutive data for all patients ≥80 years (group 2). Data were collected for patient demographics, stone characteristics, operative details, and clinical outcomes. Results: A total of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
(46 reference statements)
1
4
0
Order By: Relevance
“…Our literature review finds that URS is safe and efficacious for the octogenarian cohort. The SFR and complication rates are comparable and not dissimilar from other younger age group, as particularly described by Sinha [ 19 ] and Tamiya [ 20 ]. Comparing URS data in the elderly population and in the young (<65 years old) or very young paediatric population (<10 years), both of the studies found that surgical complication rate and successful events were similar in the different age groups.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Our literature review finds that URS is safe and efficacious for the octogenarian cohort. The SFR and complication rates are comparable and not dissimilar from other younger age group, as particularly described by Sinha [ 19 ] and Tamiya [ 20 ]. Comparing URS data in the elderly population and in the young (<65 years old) or very young paediatric population (<10 years), both of the studies found that surgical complication rate and successful events were similar in the different age groups.…”
Section: Discussionsupporting
confidence: 68%
“…The sample size ranged from 27 to 338 across 10 studies, with a mean age of studies between 81 and 89 years, with the cut-off for the lower end being 80 years. Eight of these studies focused on URS independently [ 6 , 13–16 , 19–21 ] and the other two discussed URS in conjunction with SWL [ 17 , 18 ], under a common description of ‘active stone treatment’, rendering some of the data unsuitable for inclusion in certain categories, where data could not be retrieved separately.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lasers have evolved with the advent of high-power holmium lasers, thulium fiber laser (TFL), and pulse modulation such as Moses technology [3][4][5]. There are four papers involving the use of lasers in endourology [6][7][8][9][10]. Laser efficiency and safety were compared between Holmium YAG and TFL lasers, with the latter showing higher efficiency [6].…”
mentioning
confidence: 99%
“…Laser efficiency and safety were compared between Holmium YAG and TFL lasers, with the latter showing higher efficiency [6]. Laser lithotripsy during ureteroscopy and stone fragmentation with comparative outcomes between ≤10 years and ≥80 years were examined by the second paper [7]. The results showed that while the former group had a higher incidence of repeated procedure, there was no difference in the overall stone-free rate (SFR) and complications between the groups.…”
mentioning
confidence: 99%